PEMANFAATAN TES STIFIN DALAM KEGIATAN KEPENDIDIKAN DI SD IT MADANI 2ISLAMIC SCHOOL PAYAKUMBUH - Gusti Mulia Sari; Bambang Trisno; Wita Wulandari (CV. ADIBA AISHA AMIRA, 2025)
Education is guidance given by adults to immature people to achieve a goal, namely maturity. Education is also defined as a conscious effort to develop the personality and abilities of students inside and outside school and lasts a lifetime. In order to survive, humans need education, because with education humans can develop all the potential they have. What is meant by potential is the ability or strength possessed by an individual. Meanwhile, genetic potential is the main ability of humans which can be a reference in designing the future or which things should be chosen according to our respective potential. To find out this potential, a test called the STIFIn test is carried out. The STIFIn concept can be used to help recognize our potential, apart from that, the STIFIn test can also be used to find out how a person's character is formed. In educational activities, the STIFIn test has certain benefits, starting from helping teachers in determining models, methods, learning evaluations, and so on. The aim of this research is to find out what are the benefits of the STIFIn test in educational activities, especially learning at SD IT Madani 2 Payakumbuh. The research that the researcher conducted was descriptive qualitative research, where in this research, the researcher will present a complete picture of the conditions that occur in the field